2010
DOI: 10.1089/vbz.2009.0123
|View full text |Cite
|
Sign up to set email alerts
|

Rats as Indicators of the Presence and Dispersal of Pathogens in Cyprus: Ectoparasites, Parasitic Helminths, Enteric Bacteria, and Encephalomyocarditis Virus

Abstract: Rodents play an active role in the transmission of a number of zoonoses by harboring and disseminating the pathogens involved, either through their biological materials or via their ectoparasites. Hence, the spatial and seasonal distribution of potential agents of zoonoses may be studied by examining their distribution in the rodent vectors and their ectoparasites. A surveillance was conducted in wild rodents in 51 different areas of Cyprus, an island ecosystem, to monitor the reemergence of Echinococcus granu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…(Gratz 1994, Mills 1999, Kosoy et al 2010. Although the prevalence and patterns of acquisition of these zoonotic pathogens in Norway rat populations have been described from a handful of urban locations in the United States and Europe (Webster et al 1995, Macdonald 1999, Battersby et al 2002, Easterbrook et al 2007, Antoniou et al 2010, similar reports on these co-circulating pathogens from tropical, developing countries are unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…(Gratz 1994, Mills 1999, Kosoy et al 2010. Although the prevalence and patterns of acquisition of these zoonotic pathogens in Norway rat populations have been described from a handful of urban locations in the United States and Europe (Webster et al 1995, Macdonald 1999, Battersby et al 2002, Easterbrook et al 2007, Antoniou et al 2010, similar reports on these co-circulating pathogens from tropical, developing countries are unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are a variety of factors that could influence if and when an animal enters a trap, including trapping methodology, trap environment, and characteristics of the individual rat [27]. Given marked variation among studies with regard to how trapping is carried out [19], [22], [31], [32], it is important to better understand how trapping might influence the number and characteristics of rats trapped.…”
Section: Introductionmentioning
confidence: 99%
“…This includes use of technologies such as Geographical Information Systems (GIS) that enable for geospatial analysis. Several recent studies have used GIS for zoonotic disease surveillance and risk assessment (Antoniou et al., 2010; Carbajo et al., 2009), and use of the technology in public health is common. In our study (question 13), both groups indicated that GIS was important for surveillance, with state veterinarians more enthusiastic than state public health veterinarians ( P = 0.024).…”
Section: Resultsmentioning
confidence: 99%